Localization of the First Mandibular Molar Roots in Relationship to the Mandibular Canal in Small Breed Dogs—A Tomography Imaging Study - Chia, Han; Taney, Kendall; Hoover, Don; Robertson, James B.; Villamizar-Martinez, Lenin A. (Frontiers in Veterinary Science, 2021)
The intimate relationship between the mandibular canal and the first mandibular molar tooth presents challenges when performing dentoalveolar surgical procedures due to the probability of causing iatrogenic injury to the inferior alveolar neurovascular bundle. Superimposition between the mandibular canal (MC) and the first molar (M1) tooth roots is often observed on intraoral dental radiographs in small breed dogs. However, due to the radiograph’s bidimensional nature, it is impossible to determine the buccal or lingual localization of the first molar roots with respect to the mandibular canal. Thus, this study’s objective was to determine the localization of the first molar tooth’s roots in relation to the position of the mandibular canal and their overlapping percentage with the canal in small bodyweight dogs (<15kgs) using tomographic diagnostic images. For this, cone-beam computed tomography and High-Definition Computed Tomography exams from 103 small breed dogs (under 15 kgs) were retrospectively assessed to determine the lingual or buccal localization of the first molar tooth’s roots with respect to the mandibular canal and the degree of overlap of the roots with the canal. In conclusion, most of the roots of M1 of dogs under 15 kgs were located at the MC's lingual aspect (82.7%) with an overall superimposition median with the MC of 100% and 90% for the mesial and distal roots, respectively. Straddle tooth roots were not a common anatomical presentation in the dogs of this study.